Epistemology of History Learning For Teachers of Aliyah Madrasah In Makassar - Abd Rahim Yunus; Mardyawati Yunus; Badruddin Kaddas (Journal of Research and Multidisciplinary, 2020)
This research-based service provides such a significant contribution to improving the quality of history learning for history teachers at Madrasah Aliyah in Makassar. Besides, it reinforces teachers as the front guard in outlining government policies to students in the classroom and developing the epistemology of historical learning as an effort to regenerate the nation's historical values. This research was conducted through the Participatory Action Research (PAR) approach. The application of the epistemology of learning history by the teachers of Madrasah Aliyah history in Makassar will refer to and follow the curriculum paradigm that is applied, namely the 2013 curriculum. Implementation of the 2013 curriculum, which has a typology of student development that is distinctive, makes history learning come alive because the knowledge that once seemed to be centered on the educator (teacher-centered learning) has begun to shift to learner-centered education. Even so, there are still Madrasah Aliyah teachers in Makassar who teach history and make students' brains viewed as safe deposit boxes. Learning material is transferred by teachers into the minds of students to be accommodated.